The influence of public environmental concern on corporate greenwashing: an examination of companies listed in China - Hongbo Fu; Rajah Rasiah; Guangji Wang; Yi Zhang (Environmental Research Communications)
This study investigates the impact of public environmental concern on corporate greenwashing behavior, emphasizing the underlying mechanisms. Analysis of panel data from China’s A-share listed companies (2012–2022) indicates that public scrutiny substantially curtails greenwashing. Two primary mediating mechanisms are identified: environmental penalties and green development. The environmental penalties mechanism suggests that both the strengthening of environmental penalties in the region and environmental compliance by corporate are pathways through which public environmental concern can effectively mitigate corporate greenwashing; while the green development mechanism suggests that the improvement of the level of green innovation by corporate or the greening of their investment strategies are mechanisms through which public environmental concerns can reduce corporate greenwashing. Heterogeneity analysis indicates more pronounced effects in industries with significant pollution and in environments characterized by considerable uncertainty. Non-state-owned firms exhibit heightened responsiveness to public concern compared to state-owned enterprises. This study enhances comprehension of corporate greenwashing and offers evidence for formulating distinct environmental strategies.